New challenges for the law on medically assisted reproduction: The new civil partnership and the planned regulation for sex identification - Φουντεδάκη (Katerina Fountedaki) Κατερίνα (Bioethica, 2017)
This paper focuses on the new civil partnership starting with the decision of 11.7.2013 ECHR condemning Greece because of the exclusion of same-sex couples from civil partnership. On the occasion of this condemnation a total abolition of civil partnership would be a temporary and regressive solution. By n. 4356 / 2015 the institution of civil partnership was reformed and the couple is considered as married regarding their interpersonal relations and in the remaining relationships the focus is on private autonomy. The legislative assimilation of the comrades who have signed a civil partnership with a married couple cannot work in the field of affinity with children. The regulatory model of different sex parents and the law of medically assisted reproduction are still dominant. This act of the legislature does not constitute a legal limbo but a conscious choice, which according to the writer does not infringe the principle of equality and Article 4 of the ECHR. Finally, it is important to say that a current study made by the lawmaking Committee of the Ministry of Justice for sex identification could modify a lot of things in the field of family law.